2022
DOI: 10.1038/s41597-022-01346-x
|View full text |Cite
|
Sign up to set email alerts
|

GriddingMachine, a database and software for Earth system modeling at global and regional scales

Abstract: Land and Earth system modeling is moving towards more explicit biophysical representations, requiring increasing variety of datasets for initialization and benchmarking. However, researchers often have difficulties in identifying and integrating non-standardized datasets from various sources. We aim towards a standardized database and one-stop distribution method of global datasets. Here, we present the GriddingMachine as (1) a database of global-scale datasets commonly used to parameterize or benchmark the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…We configured CliMA Land using the globally gridded data sets from GriddingMachine, which shares data sets via FTP/HTTP, Julia, Matlab, Octave, Python, and R (Wang et al., 2022). The data sets we used in the present study (labeled as “gm3”) included soil color (P. J. Lawrence & Chase, 2007), soil hydraulic parameters (Dai et al., 2019), canopy height (Simard et al., 2011), chlorophyll content (Croft et al., 2020), CI (Wei et al., 2019), leaf area index (LAI) (Yuan et al., 2011), specific leaf area (Butler et al., 2017), photosynthetic capacity (Luo et al., 2021), elevation (Yamazaki et al., 2017), land mask (Hersbach et al., 2020), and PFT map used to derive stomatal parameters (P. J. Lawrence & Chase, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…We configured CliMA Land using the globally gridded data sets from GriddingMachine, which shares data sets via FTP/HTTP, Julia, Matlab, Octave, Python, and R (Wang et al., 2022). The data sets we used in the present study (labeled as “gm3”) included soil color (P. J. Lawrence & Chase, 2007), soil hydraulic parameters (Dai et al., 2019), canopy height (Simard et al., 2011), chlorophyll content (Croft et al., 2020), CI (Wei et al., 2019), leaf area index (LAI) (Yuan et al., 2011), specific leaf area (Butler et al., 2017), photosynthetic capacity (Luo et al., 2021), elevation (Yamazaki et al., 2017), land mask (Hersbach et al., 2020), and PFT map used to derive stomatal parameters (P. J. Lawrence & Chase, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 summarizes the global scale data sets we used to configure CliMA Land and drive model simulations in the presented study (corresponding to “gm1” in our model simulations; see Figure 1 for where these parameters and variables were used). The global maps used can be accessed through GriddingMachine (https://github.com/CliMA/GriddingMachine.jl), a database and software we developed to distribute globally gridded data sets (Y. Wang et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The global scale data sets used for CliMA Land simulation (except for ERA5 data) can be accessed through GriddingMachine (https://github.com/CliMA/GriddingMachine.jl; Y. Wang et al., 2022). The exact version of CliMA Land used in the present study can be found at (Y. Wang, 2023a), and the model outputs for years 2010 and 2019 are archived at Zenodo (Y. Wang, 2023b).…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the gridded Moderate Resolution Imaging Spectroradiometer (MODIS) LAI product at 0.5° spatial resolution and 8‐day temporal resolution (Yuan et al., 2011), weekly mean leaf chlorophyll content to represent seasonality of canopy greenness (Croft et al., 2020), and assumed leaf carotenoid content being 1/7 of the chlorophyll content, specific leaf area as the inverse of leaf mass per area (Butler et al., 2017), leaf photosynthetic capacity represented by the maximum carboxylation rate at a reference temperature of 25°C (Vcmax25) from a machine learning based product (Luo et al., 2021), the maximum electron transport rate at a reference temperature of 25°C (Jmax25), and respiration rate at a reference temperature of 25°C (Rd25) scaled from Vcmax25 as Jmax25 = 1.67.Vcmax25 and Rd25 = 0.015.Vcmax25, a canopy height map was used to initialize plant hydraulic architecture within each simulation (Simard et al., 2011), and MODIS clumping index was used to represent canopy horizontal structure (Braghiere et al., 2019; He et al., 2012). Gridding Machine (Wang et al., 2022) is a tool developed for CliMA‐Land that simplifies the replacement of plant trait maps. These maps contain important information about vegetation characteristics and are crucial for accurately representing vegetation processes in the model.…”
Section: Methodsmentioning
confidence: 99%